2010
DOI: 10.1016/j.jfludis.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Temperament dimensions in stuttering and typically developing children

Abstract: After reading this article, the reader will be able to: (1) describe the concept of temperament, including Rothbart's temperamental model, and its functional significance; (2) explain the CBQ-based (Children's Behavior Questionnaire) temperamental differences between CWS and CWNS; and (3) explain possible pathways for interaction between temperament and the development of stuttering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
182
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(215 citation statements)
references
References 75 publications
(94 reference statements)
26
182
5
2
Order By: Relevance
“…Interestingly, this study showed that activity in the 15 ACC was negatively correlated with the severity of stuttering symptoms, possibly reflecting a 16 failure to recruit conflict related regions to resolve stuttering (Liu et al, 2014). 17 Even though almost no studies examined functional brain activation in children who 18 stutter, some hypotheses can be derived from studies that related stuttering in children to showing less inhibitory control in CWS (Eggers et al, 2009(Eggers et al, , 2010(Eggers et al, , 2013 time, they were shown a feedback screen with the marble at the point at which they had 14 stopped it. These trials measured stimulus-driven action and were called Green-Go trials.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, this study showed that activity in the 15 ACC was negatively correlated with the severity of stuttering symptoms, possibly reflecting a 16 failure to recruit conflict related regions to resolve stuttering (Liu et al, 2014). 17 Even though almost no studies examined functional brain activation in children who 18 stutter, some hypotheses can be derived from studies that related stuttering in children to showing less inhibitory control in CWS (Eggers et al, 2009(Eggers et al, , 2010(Eggers et al, , 2013 time, they were shown a feedback screen with the marble at the point at which they had 14 stopped it. These trials measured stimulus-driven action and were called Green-Go trials.…”
mentioning
confidence: 86%
“…This work was supported by the Dutch Science Foundation (NWO, grant number 461-090525) 2 as part of the EUROVETO project (09-ERCP-020) of the European Science Foundation.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Assuming, based on previous findings [8,11,20], that temperamental differences do exist between preschool-age CWS and CWNS, the present preliminary study examines differences in the temperament of parents of children who stutter and parents of children who do not stutter. The present study also examines the relational difference between the temperament of parents to children across both talker groups (i.e., children who stutter and children who do not stutter).…”
Section: Purpose and Hypothesismentioning
confidence: 99%
“…Findings indicated differences in mean scores, but similar underlying temperamental structures for all three groups. Eggers et al continued their investigation of temperament and stuttering by a comparison of the temperament of 3-8 year old CWS and CWNS only [20]. Findings indicated lower scores in Inhibitory Control and Attentional Shifting, but higher scores in Anger/Frustration, Approach, and Motor Activation regardless of treatment or stuttering severity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation